The Quest for Retributive Justice - Majidzadeh Heravi,Amir (2011)
The war crimes committed between 1992 and 1995 in Bosnia-Herzegovina have mainly been under the jurisdiction of the legal systems set up by the international community. To solve the atrocities of the past, institutions like the ICTY and the WCC were set up. But to this day there is estimated to be thousands of direct perpetrators still walking free in and around Bosnia-Herzegovina. The purpose of this study is to see exactly how this search for justice is progressing and what is preventing it to operate more efficiently sixteen years after the signing of the Dayton Peace Agreement. By analyzing the main international strategies in dealing with retributive justice, namely the ICTY in The Hague and the WCC in Sarajevo, I conclude that there have been consequences to the internal legal structure of Bosnia-Herzegovina and a general negative perception among the victims of the war on the attributes of retributive justice.
Keywords: transitional justice; retributive justice; the ICTY; the WCC; Bosnia-Herzegovina